Synthesis of mechanically robust renewable poly(ester-amide)s through co-polymerisation of unsaturated polyesters and synthetic polypeptides. (15th January 2020) - Brannigan, Ruairí P.; Heise, Andreas
Graphical abstract: Abstract: As an alternative to polyester-based materials, synthetic polypeptides have received a great deal of attention as bio-derived polymers for various applications. Polypeptide-based materials offer numerous advantages over traditional polyesters such as efficient and complete bio- and ecological absorption, however, poor mechanical robustness and low processability has prevented the commercial application of polypeptides. Conversely, copolymers of polyesters and polypeptides have the potential to combine the mechanical versatility of aliphatic polyesters while retaining the enhanced bio-absorption of polypeptides. Itaconic acid-based polyesters were crosslinked with modified telechelic poly(L-aspartic acid β-benzyl ester) and the amino acid-derived 2-vinyl-4, 4-dimethylazlactone in order to assess their effect on their bulk materials properties. It was found that through variance of the polymer composition that the mechanical properties and the hydrolytic degradation of the materials could be modulated. We believe that these crosslinked polymers offer a unique platform for the development of sustainable degradable materials.